Two new nepenthes species from the unexplored mountains of Central Mindanao, Philippines - Lagunday, Noel E.; Acma, Florfe M.; Cabana, Veneracion G.; Sabas, Novo M.; Amoroso, Victor B. (2017)
Nepenthes L. is the sole genus of the family Nepenthaceae. Having the highest rate of endemism of this family, the Philippines is considered a center of diversity of the genus Nepenthes along with Sumatra and Borneo. Recent explorations in Mindanao and Luzon raised the number of Philippine Nepenthes species to 50. This study reports the discovery of two new Nepenthes species, N. malimumuensis and N. manobo in the unexplored region of the Pantaron range of central Mindanao making the range a home to eight species. Habitat destruction has the biggest impact on the population of Nepenthes spp. in the Pantaron range. The Pantaron range is not a protected area therefore the diversity, distribution, conservation and habitat preservation of the new endemic Nepenthes species reported herein need to be monitored closely. (Author's abstract)